The Influence of Halal Lifestyle on Career Women in Indonesia - Annisa Yaumil Salsabila; Dwi Nur'aini Ihsan (ETIKONOMI, 2023)
The halal industry is experiencing rapid development, one of which is the increasing demand for halal products. Studying the halal lifestyle for career women is interesting because of the growing development of Muslim fashion and halal cosmetics. The originality of this research lies in a comprehensive study of the halal lifestyle in career women. This study aimed to determine the effect of religiosity, knowledge, awareness, and social environment on the halal lifestyle of career women in Jakarta Province. The respondents were 250 Muslim career women. The method of this research used the SEM-PLS method. The results of this research indicated that the variables of religiosity, awareness, and social environment significantly affect the halal lifestyle. Meanwhile, the knowledge variable does not affect the halal lifestyle. This research implies that halal industry producers must increase intense outreach and education to the public, especially among career women.JEL Classification: E31, F31, C22How to Cite:Salsabila, A. Y., & Ihsan, D. N. (2023). The Influence of Halal Lifestyle on Career Women in Indonesia. Etikonomi, 22(1), 197–212. https://doi.org/10.15408/etk.v22i1.30605.